Algunas formas de la racionalidad. El problema educativo - Rodríguez Neira, Teófilo (Teoría de la Educación. Revista Interuniversitaria, 2009)
Rationality manifests itself in different forms and rests on different principles, forms and principles which are irreducible among themselves. Each form tende to eliminate and absorb the others. In addition the forms carry within themselves exegetical and educational models. But if education is to be as fully complete as possible it cannot allow itself to be reduced. So the different forms of rationality state a fundamental educational problem: that of the specific relationship education mantains with each of them and that of the accomplishment which is necessary to establish among themselves.